Beyond Pills: A Comprehensive Approach to Primary Headaches Through Physical Activity, Physiotherapy, and Diet - Antoni Sieńko; Jakub Sadowski; Tomasz Maciejczyk; Karol Krzykawski; Julia Dołęga; Piotr Mól; Bartłomiej Zabawa; Patrycja Hudzińska; Łukasz Stanisław Papież; Małgorzata Łabuś (Quality in Sport)
Introduction: Headaches represent a significant global health issue in terms of both prevalence and the complexity of the disorder. The etiology remains unclear, with numerous factors contributing to their development. Pharmacotherapy represents the primary method of treatment, although the influence of physical activity on headache occurrence is a topic of considerable interest in the scientific literature.